ANALYSIS OF THE ROLE OF KNOWLEDGE MANAGEMENT IN IMPROVING THE SUSTAINABLE PERFORMANCE OF COFFEE SMEs: A CASE STUDY OF TAMANSARI COFFEE SMEs - Pusvita, Della; Jayanti, Rahmah (STIESA Press, 2026)
This research is motivated by the importance of knowledge management in facing business challenges and opportunities, particularly in the micro, small, and medium enterprise (MSMEs) sector. Amidst the increasingly competitive and sustainability-oriented coffee industry, the implementation of knowledge management is a key factor in improving the effectiveness and efficiency of business operations. Taman Sari Kopi, as a coffee processing MSMEs located in Subang Regency, was chosen as the study object because it has demonstrated initiative in integrating sustainability practices with independent knowledge management. The primary objective of this study is to analyze how knowledge management is applied in the context of coffee processing MSMEs, and how these practices impact business sustainability, both economically, socially, and environmentally. This study employed a descriptive qualitative approach, with data collection techniques consisting of in-depth interviews and documentation. The primary informants were MSMEs owners or managers directly involved in the production and management processes. The research results show that the implementation of good knowledge management contributes significantly to increasing production process efficiency, product innovation, and strengthening awareness of environmental and social aspects. Although there are still obstacles such as limited human resources and digital literacy, MSMEs that actively share knowledge and implement data-driven practices tend to have better sustainability performance.